2022
DOI: 10.3390/nu14224814
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Nutritional Status and Quality of Life in Chronic Kidney Disease and Kidney Transplant Patients: A Comparative Analysis

Abstract: Background: Chronic kidney disease (CKD) can significantly influence a patient’s nutritional status, leading to malnutrition. Malnutrition is associated with an increase in morbidity and hospital admissions, as well as a decrease in functional status. All these factors impact emotional, physical, and psychosocial health, leading to a lower quality of life (QOL). The aim of the study was to assess the nutritional status and QOL in patients with CKD compared to patients after kidney transplantation and determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
2
6
1
2
Order By: Relevance
“…3,11 Another study stated the prevalence of malnutrition to be 27% in RTRs according to the Mini Nutritional Assessment. 22 We found the prevalence of malnutrition to be 25.3% according to the GLIM criteria, which is similar to previous studies. A study conducted in 2021 on patients undergoing renal transplantation found that the most crucial phenotypic criterion in the GLIM criteria was reduced muscle mass, 21 whereas we found in our study the most common criterion to be weight loss.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…3,11 Another study stated the prevalence of malnutrition to be 27% in RTRs according to the Mini Nutritional Assessment. 22 We found the prevalence of malnutrition to be 25.3% according to the GLIM criteria, which is similar to previous studies. A study conducted in 2021 on patients undergoing renal transplantation found that the most crucial phenotypic criterion in the GLIM criteria was reduced muscle mass, 21 whereas we found in our study the most common criterion to be weight loss.…”
Section: Discussionsupporting
confidence: 91%
“…Two other studies that assessed malnutrition in RTRs via the Subjective Global Assessment and Malnutrition‐Inflammation Score found that 28% and 52% were malnourished, respectively 3,11 . Another study stated the prevalence of malnutrition to be 27% in RTRs according to the Mini Nutritional Assessment 22 . We found the prevalence of malnutrition to be 25.3% according to the GLIM criteria, which is similar to previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…The full form of the MNA contains 18 items and assesses four different aspects: anthropometric assessment (BMI, weight loss, and arm and calf circumferences), general assessment (lifestyle, medications taken, mobility, and presence of signs of depression or dementia), short dietary assessment (number of meals, protein and uid intake, and autonomy of feeding), and subjective assessment (selfperception of health and nutrition, self-assessment of health compared to peers). By adding up the scores, labelled as MNA-LF, individuals are divided into three groups using threshold values of < 17 for "malnourished," 17-23.5 for "at risk of malnutrition" and ≥ 24 for "normal nutritional status," with a maximum total score of 30 points [24,25].…”
Section: Mini Nutritional Assessmentmentioning
confidence: 99%
“…Patients with chronic kidney disease (CKD), especially those with end-stage renal disease (ESRD), are highly susceptible to malnutrition ( 1 ), resulting in a decreased quality of life ( 2 ). Patients with CKD face increased risks of worsening their prognosis owing to nutrition-related issues, including cachexia and protein-energy wasting (PEW).…”
Section: Introductionmentioning
confidence: 99%